Association of ORMDL3 with rhinovirus‐induced endoplasmic reticulum stress and type I Interferon responses in human leucocytes. Issue 3 (March 2017) - Liu, Y.‐P.; Rajamanikham, V.; Baron, M.; Patel, S.; Mathur, S. K.; Schwantes, E. A.; Ober, C.; Jackson, D. J.; Gern, J. E.; Lemanske, R. F.; Smith, J. A.
Summary: Background: Children with risk alleles at the 17q21 genetic locus who wheeze during rhinovirus illnesses have a greatly increased likelihood of developing childhood asthma. In mice, overexpression of the 17q21 gene ORMDL3 leads to airway remodelling and hyperresponsiveness. However, the mechanisms by which ORMDL3 predisposes to asthma are unclear. Previous studies have suggested that ORMDL3 induces endoplasmic reticulum (ER) stress and production of the type I interferon (IFN)‐regulated chemokine CXCL10. Objective: The purpose of this study was to determine the relationship between ORMDL3 and rhinovirus‐induced ER stress and type I IFN in human leucocytes. Methods: ER stress was monitored by measuring HSPA5, CHOP and spliced XBP1 gene expression, and type I IFN by measuring IFNB1 (IFN‐β) and CXCL10 expression in human cell lines and primary leucocytes following treatment with rhinovirus. Requirements for cell contact and specific cell type in ORMDL3 induction were examined by transwell assay and depletion experiments, respectively. Finally, the effects of 17q21 genotype on the expression of ORMDL3, IFNB1 and ER stress genes were assessed. Results: THP‐1 monocytes overexpressing ORMDL3 responded to rhinovirus with increased IFNB1 and HSPA5 . Rhinovirus‐induced ORMDL3 expression in primary leucocytes required cell–cell contact, and induction was suppressed by plasmacytoid dendritic cell depletion. The degree of rhinovirus‐induced ORMDL3, HSPA5 and IFNB1 expression varied by leucocyte type and 17q21 genotype, with the highest expression of these genes in the asthma‐associated genotype. Conclusions and Clinical Relevance: Multiple lines of evidence support an association between higher ORMDL3 and increased rhinovirus‐induced HSPA5 and type I IFN gene expression. These associations with ORMDL3 are cell type specific, with the most significant 17q21 genotype effects on ORMDL3 expression and HSPA5 induction evident in B cells. Together, these findings have implications for how the interaction of increased ORMDL3 and rhinovirus may predispose to asthma.